Odpowiedzi

2010-02-27T15:13:15+01:00
1⅙-(-2¹/₁₂)=¹⁴/₁₂+²⁵/₁₂=³⁹/₁₂=3¼

3,7-4⅖=3,7-4,4=-0,7

(-⅞)+(-0,7)=-0,875-0,7=-1,575

1,4-(-1¾)=1,4+1,75=3,15

(-2⅙)-(-1,6)=-¹³/₆+⁸/₅=-⁶⁵/₃₀+⁴⁸/₃₀=-¹⁷/₃₀
1 5 1
2010-02-27T15:17:37+01:00
A) 1i1/6-(-2i1/12) = 7/6 + 25/12 =14/12 + 25/12 = 39/12 = 3 i 1/4
b) 3,7-4i2/5 = 37/10 - 44/10 = -7/10
c) (-7/8)+(-0.7) = -7/8 - 10/7 = -49/56 - 80/56 = -31/56
d) 1,4-(-1i3/4) = 14/10 + 7/4 = 56/40 + 70/40 = 126/40 = 3 i 3/20
e) (-2i1/6)-(-1,6) = - 13/6 + 16/10 = - 130/60 + 96/60 = -40/60 = - 4/6 = -2/3
2010-02-27T15:20:32+01:00
1i1/6-(-2i1/12)=1 1/6+2 2/12=1 1/6+2 1/6=3 2/6=3 1/3
3,7-4i2/5=3 7/10-4 4/10=-7/10
(-7/8)+(-0.7)=-7/80-56/80=-63/80
1,4-(-1i3/4)=1 8/20+1 15/20=3 3/20
(-2i1/6)-(-1,6)=-2 5/30+1 18/30=-17/30